Public health over private wealth: rebalancing public and private interests in international trade and investment agreements - Ashley Schram; Belinda Townsend; Jeremy Youde; Sharon Friel (Sax Institute, 2019)
The emerging global trade and investment regime is a site of ongoing contestation between states, powerful industry actors and civil society organisations seeking to influence the formation of legal rules, principles, practices and institutions. The inclusion of major transnational tobacco, alcohol and ultraprocessed food companies seeking to influence governments in these processes has resulted in the expanded distribution and consumption of unhealthy commodities across the globe, overshadowing many of the positive impacts for health hypothesised from liberalised trade. The growing number of pathways for market actors to exert undue influence over national and international regulatory environments provided by agreements, such as the Comprehensive and Progressive Agreement for Trans-Pacific Partnership, has given many cause to be concerned. In the context of continued commitment by states to international trade and investment negotiations, we present several avenues for public health scholars, advocates and practitioners to explore to rebalance public and private interests in these deals.